Effect of the concentration on dynamic properties of single-charged electrolytes - Atamas, N. O.; Bulavin, L.A.; Brytan, A.; Verbynska, G.M. (Reports of the National Academy of Sciences of Ukraine, 2015)
The results of the experimental (quasielastic neutron scattering) and theoretical-computational (molecular dynamics) studies of the effect of the concentration on structural and dynamical properties of aqueous solutions of NaCl at T = 300 K are presented. It is experimentally shown that increasing the concentration of the studied system leads to a monotonic decrease of the coefficient of self-diffusion, its components, and the times of sedentary molecules in equilibrium, as confirmed by the results of computer simulation. The mechanisms of formation of the structure of solutions at various concentrations are analyzed, and the quantitative characteristics of a local structure and the diffusion coefficients of components of the system under study are calculated for some separate regions.